Modern Adaptive and Intelligent Digital Learning Systems: Mechanisms and Potential - Konstantin A. Skvorchevsky; Olga V. Dyatlova (Вопросы образования)
This article examines the necessary elements of an adaptive system - the knowledge domain model, the user model, adaptivity mechanism, and explanation model - and the impact of each on the potential effectiveness of existing and potentially possible systems.